2021
DOI: 10.24850/j-tyca-2021-03-03
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemical and microbiological water quality on bacterial community assemblage of San Juan River (Sierra del Rosario, Biosphere Reserve, Cuba)

Abstract: The objective of the present study was to analyze the influence of different physicochemical and microbiological indicators on bacterial assemblages in a freshwater ecosystem located in a Biosphere Res erve.The bacterioplankton communities composition was determined by denaturing gradient gel electrophoresis (DGGE) of 16S rDNA during three sampling campaigns in three sampling stations of San Juan Ri ver.Multivariate statistical analyses of gel patterns, in relat i on t o chemi cal , biological and physical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Havana and receives little or no treatment wastewater of domestic and industrial origin from the city that contributes to the pollution of the ecosystem(Romeu et al 2015b). The high phosphate concentrations determined in the Almendares River [seeIzquierdo et al (2020) and Online Resource 3 for values of physicochemical and microbiological indicators] contributed to the high NPI values obtained in this study.In the case of the San Juan River, the NPI indicated that this is a moderately polluted ecosystem (Table1), which is in correspondence with previous studies carried out in this river(Izquierdo et al 2020;Larrea et al 2021). The San Juan River is located in the province of Artemisa, in the "Sierra del Rosario" Biosphere Reserve, where it does not receive the same anthropogenic impact as the Almendares River because it is in a rural area where there is no presence of industries.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Havana and receives little or no treatment wastewater of domestic and industrial origin from the city that contributes to the pollution of the ecosystem(Romeu et al 2015b). The high phosphate concentrations determined in the Almendares River [seeIzquierdo et al (2020) and Online Resource 3 for values of physicochemical and microbiological indicators] contributed to the high NPI values obtained in this study.In the case of the San Juan River, the NPI indicated that this is a moderately polluted ecosystem (Table1), which is in correspondence with previous studies carried out in this river(Izquierdo et al 2020;Larrea et al 2021). The San Juan River is located in the province of Artemisa, in the "Sierra del Rosario" Biosphere Reserve, where it does not receive the same anthropogenic impact as the Almendares River because it is in a rural area where there is no presence of industries.…”
supporting
confidence: 90%
“…All of which leads to the eutrophication conditions that this river presents(Arpajón et al 2011). In the San Juan River, the limitation by phosphate implies higher concentrations of nitrate, less addition of phosphates from polluting sources and therefore, less risk of eutrophication and better water quality(Izquierdo et al 2020;Larrea et al 2021).…”
mentioning
confidence: 99%